The Effect of Cultural Factor on the Architectural Characteristics of the Traditional Houses Traditional Houses in Sulaymaniyah City (1900-1940), as case study - كاني محمد محمد صالح; Dr. Alan Faraidun Ali (Sulaimani Journal for Engineering Sciences)
Culture and cultural changes have influenced architectural form throughout the ages, especially for residential houses, transforming their shape and content. This is due to a significant change in cultural heritage, values, customs, and traditions. This is a result of the influence of cultural elements and their components on the architectural and local character. The civilizational and cultural development of the built environment changes as a result of technological development, along with beliefs and lifestyles that vary across ages and times. Therefore, keeping pace with the basic heritage without abandoning the origins is necessary. This research addresses the most important descriptive and analytical historical studies specialized in the impact of cultural factors on changing the characteristics of houses in the city of Sulaymaniyah. Therefore, to understand the characteristics and architectural form of houses, the research focused on studying the cultural factor and its influence on traditional residential houses in Sulaymaniyah. Thus, the research problem emerged, which is the lack of knowledge about the role of this factor in the architectural characteristics that are distinguished by formal architectural characteristics that distinguish them as part of the local and global culture in the city of Sulaymaniyah. The research aims to clarify the importance of the impact of the cultural factor on the architectural characteristics of traditional residential houses and to extract the formal characteristics of the architecture of traditional residential houses, which are useful in the field of application in future projects in a contemporary manner, especially in the city of Sulaymaniyah. The research hypothesized that the influence of the cultural factor on architectural and formal characteristics stems from the nature of the specific cultural elements, in addition to the influence of human and societal cultural elements in bringing about changes in these aspects. Within its theoretical framework, the research adopted the (structural approach) to reveal the variables of cultural factors in the design process. This framework was applied to architectural models of selected traditional residential houses from the city of Sulaymaniyah, leading to the analysis of results and the identification of conclusions. The research concluded that there is a close link between culture and architecture in the city of Sulaymaniyah and how traditional houses reflect the identity, social thought, and local history .